2016
DOI: 10.1002/clen.201500532
|View full text |Cite
|
Sign up to set email alerts
|

Chromium and Aluminum Phytotoxicity in Maize: Morpho‐Physiological Responses and Metal Uptake

Abstract: The present study investigated the uptake, translocation, and accumulation of chromium (Cr 6þ ) and aluminum (Al 3þ ) in maize and their induced variations in morpho-physiological and biochemical attributes as well as growth behavior and yield formation. Plants were grown in pots supplied with heavy metals, alone and in combination (chromium (Cr), aluminum (Al) and chromium þ aluminum (Cr þ Al)) while pots without adding Cr or Al were regarded as control. Metal stress considerably reduced growth and yield rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…Furthermore, ROS contents were also increased significantly when plants were exposed to individual Cu treatment (Tables 2 and 3 ), which is supported by previous studies conducted by Feigl et al [ 31 ] in which a significant ROS level was produced in both Brassica species treated with Cu. Besides this, ROS concentration increased further under combined treatment of Cu and Cr, which is also in line with the previous studies, where the combined treatment of Cr or Cu with other metals proved to be more toxic than their alone treatments [ 32 , 33 ]. Additionally, the accumulation of ROS in different stress treatments was correlated with the results of histochemical staining of NBT (O 2 ∙− ) and DAB (H 2 O 2 ) ( Figure 1 ).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, ROS contents were also increased significantly when plants were exposed to individual Cu treatment (Tables 2 and 3 ), which is supported by previous studies conducted by Feigl et al [ 31 ] in which a significant ROS level was produced in both Brassica species treated with Cu. Besides this, ROS concentration increased further under combined treatment of Cu and Cr, which is also in line with the previous studies, where the combined treatment of Cr or Cu with other metals proved to be more toxic than their alone treatments [ 32 , 33 ]. Additionally, the accumulation of ROS in different stress treatments was correlated with the results of histochemical staining of NBT (O 2 ∙− ) and DAB (H 2 O 2 ) ( Figure 1 ).…”
Section: Discussionsupporting
confidence: 91%
“…4a) which may be the result of chlorophyll degradation (Farooq et al 2009), as drastic reductions in chlorophyll contents were reported in developing leafs due to consistent chilling stress in maize (Fryer et al 1998). Chlorophyll contents, electrolyte leakage in plasma membrane, and internal moisture status of plants gave valued information about the physiological status of plants (Anjum et al 2016b). Enhanced total chlorophyll and relative water contents with improved rates of photosynthesis and transpiration in maize plants sprayed exogenously by MLE and SA (Figs.…”
Section: Discussionmentioning
confidence: 98%
“…Cytosolic accumulation of osmolytes is important to maintain cell turgor and involved in osmoregulation ( Anjum et al, 2016 ). Our results indicated that GABA application enhanced protein contents in leaves of all maize cultivars while lowered in roots ( Figure 5 ) whilst accumulation of proline concentration remained non-significant ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, generation of ROS often caused membrane damage and disintegration of various cellular structures and organelles thus cause ultimate cell death ( Mittler et al, 2004 ; Ashraf et al, 2015 ; Anjum et al, 2016 ), however, timely action of SOD and POD against ROS in GABA treated maize seedlings to protect membrane damage indicated potential of GABA to in maintaining cell integrity. GABA-induced maintenance of higher activities of anti-oxidants is crucial to improve plants’ ability against oxidative stress.…”
Section: Discussionmentioning
confidence: 99%